1996
DOI: 10.1002/(sici)1097-0231(199610)10:13<1688::aid-rcm717>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

New Immobilization Chemistry for Probe Affinity Mass Spectrometry

Abstract: Probe affinity mass spectrometry (PAMS) is a technique that combines affinity separations directly with matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). In this approach, a binding molecule, such as an antibody, lectin or receptor, is covalently attached to the surface of a MALDI probe. This permits the analyte of interest to be selectively captured and concentrated on the probe surface prior to MALDI-MS analysis. A major limitation of our initial PAMS immobilization chemistry was that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 1 publication
(2 reference statements)
1
57
0
Order By: Relevance
“…The insulin peaks could be resolved from the background (≥3 times of baseline intensity) even when the insulin level was as low as 0.8 nM. The limit of detection (LOD) at 0.8 nM obtained in standard solution is much lower than the previous reported similar works, in which the tested peptide levels were usually at the range of micromole [25] or several hundred nano-moles [24]. A good linear correlation (R 2  = 0.994) of MS intensity with insulin level was obtained in the range of 0.8–48 nM (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The insulin peaks could be resolved from the background (≥3 times of baseline intensity) even when the insulin level was as low as 0.8 nM. The limit of detection (LOD) at 0.8 nM obtained in standard solution is much lower than the previous reported similar works, in which the tested peptide levels were usually at the range of micromole [25] or several hundred nano-moles [24]. A good linear correlation (R 2  = 0.994) of MS intensity with insulin level was obtained in the range of 0.8–48 nM (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…A small number of studies have reported the use of this strategy to detect insulin [2325]. In these reported methods, the antibody of target analyte was immobilized on 2-dimension planar substrate by using complicated chemical reagents [23, 24] or non-specific adsorption [25]. However, the surface area of 2-dimension planar substrate was restricted, limiting the number of immobilized antibodies and the approach of target analytes [2325].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In probe affinity mass spectrometry (PAMS), a binding molecule (e.g., antibody, lectin, or receptor) is covalently bound to the surface of the MALDI probe allowing for selective capture and concentration on the probe surface before mass spectrometric analysis (Brockman & Orlando, 1995). Different methods of surface functionalization (Brockman & Orlando, 1996), including photoimmobilization (Janecki, Broshears, & Reilly, 2004), can now be used to attach proteins onto surfaces. Wang, Tseng, and Lebrilla (1999) introduced a general concept for producing bioaffinity MALDI probes that could be useful in analyte preconcentration, extraction or purification.…”
Section: Basic Analytical Steps Performed On Platementioning
confidence: 99%
“…These on-MALDI-target sample fractionation approaches typically involve direct modification of the target surface to incorporate a selective affinity capture motif, based on either bioselectivity or chemical selectivity. 4,5,6 One limitation of these on-MALDI-target fractionation approaches, is the inherent low loading capacities of the modified target surfaces, which may be limited to as little as a monolayer of captured analyte, or even lower. In an effort to address this limitation, while retaining the advantages of the on-MALDI-target approach, our research has focused on the development of functional brush-polymer modified MALDI targets.…”
Section: Introductionmentioning
confidence: 99%